Evaluation of Data and Tools from CGIAR Research Program on Climate Change, Agriculture, and Food Security (CCAFS) - Nelson, S.; Brown, V.; Cuéllar, E.; Fox, K (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
This report assesses nine CCAFS tools/datasets in terms of who is using them and for what purposes, and explores whether and how the use of CCAFS data and tools has contributed to outcomes, in particular to changes in knowledge, attitude or skills, as well as potential changes in behaviour and practice among different user groups, where possible.